ANALISIS LITERASI DIGITAL CALON GURU SD DALAM PEMBELAJARAN BERBASIS VIRTUAL CLASSROOM - Yudhie Suchyadi; Fitri Siti Sundari; Rahma Alfiani (Universitas Pakuan, 2021)
ANALYSIS OF DIGITAL LITERACY FOR ELEMENTARY SCHOOL TEACHER CANDIDATES IN VIRTUAL CLASSROOM BASED LEARNINGAbstract. Self-directed learning is a process in which individuals learn without the help of others supported by digital and cellular technology, technology applications are developed to take advantage of the concept of independent learning. By implementing online learning strategies, digital literacy skills are absolutely needed by students. This is because it is impossible to implement online learning without being supported by high digital literacy. This study aims to describe the digital literacy of elementary school teacher education students in virtual classroom-based learning. The method used is descriptive qualitative research with a sample of 74 PGSD students. The results showed that most students had basic internet skills, PGSD students were able to find and retrieve information from the internet, and use it effectively.